Enhanced copper micro/nano-particle mixed paste sintered at low temperature for 3D interconnects - Gan, Chee Lip (2017)
An enhanced copper paste, formulated by copper micro- and nano-particles mixture, is reported to prevent paste cracking and obtain an improved packing density. The particle mixture of two different sizes enables reduction in porosity of the micro-paste and resolves the cracking issue in the nano-paste. In-situ temperature and resistance measurements indicate that the mixed paste has a lower densification temperature. Electrical study also shows a ∼12× lower sheet resistance of 0.27 Ω/sq. In addition, scanning electron microscope image analysis confirms a ∼50% lower porosity, which is consistent with the thermal and electrical results. The 3:1 (micro:nano, wt. %) mixed paste is found to have the strongest synergistic effect. This phenomenon is discussed further. Consequently, the mixed paste is a promising material for potential low temperature 3D interconnects fabrication.